The association of exclusive breastfeeding with early child development: secondary analysis of a cohort study using the deuterium oxide dose-to-mother technique - Sofa Rahmannia; R Siti Amalia; Mia Miranda; Aly Diana (Paediatrica Indonesiana, 2026)
Background The World Health Organization (WHO) recommends exclusive breastfeeding during the first six months of life to support optimal growth and development. Evidence from Indonesia on how exclusive breastfeeding affects various developmental domains remains limited, particularly those using objective methods to assess breastfeeding practices. Objective To examine the association between exclusive breastfeeding during early infancy and child developmental outcomes across multiple domains in an Indonesian cohort. Methods This study used secondary data from a cohort study 221 mother–infant pairs in Bandung and Sumedang, Indonesia. Breastfeeding status at 2 and 5 months was determined in the parent cohort using the deuterium oxide dose-to-mother (DTM) method. Child development was assessed at 2, 5, 12, and 18 months using the Ages and Stages Questionnaire, Third Edition (ASQ-3), across five domains: communication, gross motor, fine motor, social, and problem-solving. Outcomes were classified as age-appropriate or not. Nutritional status and morbidity were also assessed and considered as potential covariates. Results Exclusive breastfeeding at five months was associated with improved fine motor development at 18 months (OR 3.3; 95%CI 1.5 to 7.6; P=0.003). No associations were observed for communication, gross motor, social, or problem-solving domains. Nutritional status and sociodemographic factors did not show significant confounding effects in bivariate analysis. Conclusion Exclusive breastfeeding during early infancy was associated with improved fine motor development at 18 months in this Indonesian cohort. These findings support ongoing efforts to promote exclusive breastfeeding as part of early childhood development strategies.